2016
DOI: 10.3389/fnana.2016.00029
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Direct Subcortical Cerebellum-Basal Ganglia Connections in Human Brain as Revealed by Constrained Spherical Deconvolution Tractography

Abstract: The connections between the cerebellum and basal ganglia were assumed to occur at the level of neocortex. However evidences from animal data have challenged this old perspective showing extensive subcortical pathways linking the cerebellum with the basal ganglia. Here we tested the hypothesis if these connections also exist between the cerebellum and basal ganglia in the human brain by using diffusion magnetic resonance imaging and tractography. Fifteen healthy subjects were analyzed by using constrained spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 61 publications
11
78
0
Order By: Relevance
“…These data extend previous works showing that CSD is a robust technique for the in vivo reconstruction of the intricate and complex brain networks (Lambert et al, 2012; Arrigo et al, 2014; Milardi et al, 2015a,b, 2016a,b; Mormina et al, 2015; Cacciola et al, 2016, 2017). …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These data extend previous works showing that CSD is a robust technique for the in vivo reconstruction of the intricate and complex brain networks (Lambert et al, 2012; Arrigo et al, 2014; Milardi et al, 2015a,b, 2016a,b; Mormina et al, 2015; Cacciola et al, 2016, 2017). …”
Section: Discussionsupporting
confidence: 88%
“…Using this approach, we have recently shown that a consistent reconstruction of the basal ganglia, red nucleus, claustrum and limbic connectome is feasible (Arrigo et al, 2014; Milardi et al, 2015a,b, 2016a,b; Mormina et al, 2015; Cacciola et al, 2016, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…For the subthalamic nucleus, recent findings reveal the existence of an anatomical substrate for the bidirectional communication between cerebellum and basal ganglia, as shown in rats (Ichinohe et al 2000) and monkeys (Bostan et al , 2013 sending disynaptic projections to the cerebellar cortex by way of the pontine nuclei. Similar evidence has been recently reported in the human brain (Pelzer et al 2013;Milardi et al 2016), consciously that these techniques are not able to dissolve direct synaptic relay. Next to a direct basal ganglia-cerebellar communication, the dentate nucleus sends efferent projections to the subthalamic region via red nucleus.…”
Section: Extrathalamic Cerebello-bg Communicationsupporting
confidence: 85%
“…Nevertheless, next to putatively overlapping regions, however, also direct communication in the human brain between basal ganglia and cerebellum, via the internal part of the pallidum, has been described by (Milardi et al 2016;Pelzer et al 2013), which is in accordance with transneuronal tracing studies in nonhuman primate studies (Hoshi et al 2005).…”
Section: Studies In the Human Speciesmentioning
confidence: 52%
“…15,16 More recently, we used constrained spherical deconvolution (CSD)-based tractography, a diffusion MRI-based technique allowing in vivo reconstruction of connectivity patterns between nervous structures, [17][18][19][20][21] to study the human analogues of the above-mentioned direct cortico- 22 and dento-pallidal projections. 23 These connections, likely paralleled by analogue cortico- 24 and dento-nigral 23,25 pathways, may exert a converging influence of cerebral and neocerebellar cortex on the basal ganglia output nuclei.…”
mentioning
confidence: 99%